The Value of Automated Follicle Volume Measurements in IVF/ICSI - Vandekerckhove, Frank; Bracke, Victoria; De Sutter, Petra (Frontiers in Surgery, 2014)
Background/Aims: The objective of this literature study is to investigate the place of recent software technology Sonography-based Automated Volume Count (SonoAVC)) for the automatic measurement of follicular volumes in IVF/ICSI. Its advantages and disadvantages and potential future developments are evaluated. Methods: A total of 74 articles were read via a Pubmed literature study. The literature study included 53 articles, 32 of which for the systematic review. Results: The SonoAVC software shows excellent accuracy. Comparing the technology with the ‘golden standard’ two-dimensional (2D) manual follicle measurements, SonoAVC leads to a significantly lower intra- and inter observer variability. However, there is no significant difference in clinical outcome (pregnancy rate). We noted a significant advantage in the time gained, both for doctor and patient. Thanks to storing the images, the technology offers the possibility of including a quality control and continuous training and further standardisation of follicular monitoring can be expected. Ovarian reserve testing by measuring the antral follicle count (AFC) with SonoAVC is highly reliable. Conclusion: This overview of previously published literature shows how SonoAVC offers advantages for clinical practice, without losing any accuracy or reliability. Doctors should be motivated to the general use of follicular volumes instead of follicular diameters.